2011
DOI: 10.1111/j.1439-0469.2011.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric differentiation among haplochromine cichlid fish species of a satellite lake of Lake Victoria

Abstract: Lake Victoria holds a young but species‐rich assemblage of cichlid fishes, which form a monophyletic assemblage with additional species from surrounding water bodies, termed the Lake Victoria superflock. Lake Victoria is surrounded by smaller lakes that are somewhat disconnected from the main lake. Lake Kanyaboli is such a small lake, having markedly reduced species diversity, in part comprised of Lake Victoria species and endemics. Here, we studied the modern haplochromine component of the cichlid fauna, repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 61 publications
3
6
0
Order By: Relevance
“…The results of our comparative morphological analysis (Odhiambo et al. 2011) corroborated the original strategy to collect and analyse all unidentifiable specimens, in that almost all collected adult specimens that did not fall within any of the already recognized species clustered in one homogenous cloud separated somewhat from A. nubila and X. phytophagus (figure 6b in Odhiambo et al. 2011).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The results of our comparative morphological analysis (Odhiambo et al. 2011) corroborated the original strategy to collect and analyse all unidentifiable specimens, in that almost all collected adult specimens that did not fall within any of the already recognized species clustered in one homogenous cloud separated somewhat from A. nubila and X. phytophagus (figure 6b in Odhiambo et al. 2011).…”
Section: Discussionsupporting
confidence: 72%
“…The recently published geometric morphometric analysis of the same individuals showed clear morphological differences between L. maxillaris and A. sp . ‘ Bigeye ’ but could not clearly separate X. phytophagus , A. nubila and the unidentified specimens in morphospace, despite their clear differentiation in terms of colour and feeding ecology (Odhiambo et al. 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenotypic plasticity is described as the environmentally sensitive production of alternative phenotypes by given genotypes (DeWitt and Scheiner ). Plasticity is a common phenomenon in cichlids and laboratory experiments have confirmed the ability of many cichlid species to change the jaw apparatus in response to different diets (Witte ; Hoogerhoud ; Meyer ; Wimberger ; Huysseune ; Smits et al ; Bouton et al ; Stauffer and Van Snik Gray ; Kerschbaumer et al ; Muschick et al ; Gunter et al ), although different diets in the wild do not always lead to divergence in morphology in cichlids (see Odhiambo et al ). Some of these studies tested plasticity of the premaxilla and showed a shorter ascending arm and a larger angle β of the premaxilla as a phenotypic response to a feeding style involving manipulation of prey (especially biting, Witte ; Wimberger ; Bouton et al ).…”
Section: Discussionmentioning
confidence: 99%